Green synthesized (Ocimum sanctum and Allium sativum) Ag-doped cobalt ferrite nanoparticles for antibacterial application. (March 2019) - Mahajan, Palak; Sharma, Aashima; Kaur, Baljeet; Goyal, Navdeep; Gautam, Sanjeev
Abstract: Cobalt ferrite and silver doped cobalt ferrite, Ag x Co1− x Fe2 O4, (x = 0, 0.005, 0.01, 0.02) nanoparticles were synthesized through sol-gel auto-combustion technique via chemical and green synthesis (using the extract of tulsi seeds( Ocimum sanctum ) and garlic cloves( Allium sativum )). Systematic characterization by XRD, FTIR, FE-SEM and EDX has been performed to study structural, morphological and magnetic behavior of the prepared samples. XRD confirms that the prepared samples are crystalline and have a cubic (inverse spinel) structure. Absorption bands have been studied using FTIR that further confirms the formation of single phase spinel crystal structure having two sub-lattices (T d and O h ). FE-SEM micrographs reveal the formation of cubic and encapsulated type structure in case of chemical and green synthesis respectively. EDX confirms the presence of all the required elements in the respective stoichoimetric ratios. Magnetic measurements through VSM at room temperature show that the magnetic saturation values for samples obtained using tulsi seed extract mediated synthesis and chemical synthesis are much higher than those obtained using garlic extract. The antibacterial activity of all the prepared samples against gram positive and gram negative strains were investigated and a modified mechanism of action for the antibacterial activity is proposed. Graphical abstract: Schematic representation of chemically and green synthesized antibacterial cobalt ferrite nanoparticle. Tulsi mediated synthesis of Ag-doped cobalt ferrite nanoparticles were found to be more potent than garlic and chemically synthesized samples.Image 1 Highlights: Synthesis of nanoparticles via various methods, chemical and green synthesis route. Characterization by XRD, FTIR, EDX and FESEM confirms the formation of the cobalt ferrites. XRD Rietveld refinement confirms purity of samples i.e. no secondary phase formation. The variation in magnetic studies shows mechanism of enhancement in activity. Modified ROS mechanism is proposed for antibacterial activity for chemical and green synthesized samples.